Perilaku Pemilihan Moda Transportasi Pekerja Komuter: Studi Kasus Jabodetabek - Irjayanti, Amelia Dertta; Sari, Dyah Wulan; Rosida, Ismatulloh (UI Scholars Hub, 2021)
Using Greater Jakarta Commuter Survey data published by Statistics Indonesia in 2014, this study aims to identify the factors affecting commuting workers to choose the mode of transportation for work and the marginal effect of these factors. Estimation results from logistic regression indicate that income and workdays are not significantly affecting the commuting workers mode choice. The number of modes used has the highest impact on the probability of private vehicle and motorcycle use over public transport. As age, time travel, and travel distance increase, commuter worker less likely to use private vehicle.